Integrating Seven Tools and Kaizen Approach in Evaluating Defects on Tofu Production Process - Ahmad Dziky Wardana; Nina Mahbubah (Politeknik Piksi Ganesha Indonesia, 2022)
UKM Tofu ADA is a tofu producer that makes an effort to develop the quality standardization of the tofu production process. Managing tofu quality through maintaining the production process is challenging, resulting in no good tofu. Defective products cause economic loss and the inability to fulfill customer orders. This study aims to evaluate defects in the tofu production process using the Seven Tools and Kaizen approach. The results of this study configure three types of product defects. Namely, mushy, cracked, and crushed. The highest percentage of defects is mushy tofu, with 43.8%. The proposed improvement using kaizen analysis is the Kaizen Five-M Checklist.